Higher Dihydrotestosterone Is Associated with the Incidence of Lung Cancer in Older Men - Chan, Y.; Alfonso, Helman; Chubb, S.; Handelsman, D.; Fegan, P.; Hankey, G.; Golledge, J.; Flicker, L.; Yeap, B. (2017)
© 2017, Springer Science+Business Media New York. Advancing age is associated with increased cancer incidence, but the role of sex hormones as risk predictors for common cancers in older men remains uncertain. This study was performed to assess associations of testosterone (T), dihydrotestosterone (DHT) and estradiol (E2), with incident prostate, lung and colorectal cancer in community-dwelling older men. Plasma T, DHT and E2 were assayed using liquid chromatography-mass spectrometry between 2001 and 2004 in 3690 men. Cancer outcomes until 20 June 2013 were ascertained using data linkage. Analyses were performed using proportional hazards competing-risks models, and adjustments were made for potential confounding factors including smoking status. Results are expressed as subhazard ratios (SHR). There were 348, 107 and 137 cases of prostate, lung and colorectal cancers respectively during a median of 9.1-year follow-up. Mean T was comparable in current and non-smokers, whilst mean DHT was lower in ex- and current smokers compared to non-smokers. After adjusting for confounders including smoking, higher T or DHT was associated with an increased incidence of lung cancer (SHR = 1.30, 95% CI 1.06–1.60; p = 0.012 per 1 SD increase in T and SHR = 1.29, 95% CI 1.08–1.54; p = 0.004 for DHT). Sex hormones were not associated with prostate or colorectal cancer. In older men, higher T or DHT predict increased incidence of lung cancer over the next decade. Sex hormones are not associated with incident prostate or colorectal cancer. Further studies are warranted to determine if similar associations of sex hormones with lung cancer are present in other populations and to investigate potential underlying mechanisms.